The Optimized Fabrication of a Novel Nanobubble for Tumor Imaging - Zhang, Jiaqi; Chen, Yihan; Deng, Cheng; Zhang, Li; Sun, Zhenxing; Wang, Jing; Yang, Yali; Lv, Qing; Han, Wei; Xie, Mingxing (Frontiers in Pharmacology, 2019)
Nanobubbles with a size of less than 1 µm can be used as ultrasound contrast agents for diagnosis and as drug/gene carriers for therapy. However, the optimal method of preparing uniform-sized nanobubbles is considered controversial. In this study, we developed a novel biocompatible nanobubbles by performing differential centrifugation to isolate the relevant subpopulation from the parent suspensions. Compared with the method of modulating the thickness of the phospholipid film without centrifugation, nanobubbles fabricated under the optimal centrifugation conditions exhibited a uniform bubble size, good stability, and low toxicity. In vitro ultrasound imaging, nanobubbles displayed excellent enhancement ability, which was comparable to microbubbles. In vivo experiment, the video intensity of nanobubbles in tumors were stronger than those of microbubbles at different times (5 min, 163.5±8.3 a.u. vs 143.2±7.5 a.u., P < 0.01; 15 min, 125.4±5.2 a.u. vs 97.3±4.6 a.u., P < 0.01). Fluorescence imaging obtained by confocal laser scanning microscopy demonstrated obviously more nanobubbles passed through vessel wall into the extravascular and intercellular space of tumors, compared with microbubbles. In conclusion, by this optimal centrifugation method, it will broaden the future applications of nanobubbles in imaging and therapy.